Oral Aminoacids Supplementation Improves Corneal Reinnervation After Photorefractive Keratectomy: A Confocal-Based Investigation - Roszkowska, Anna M; Rusciano, Dario; Inferrera, Leandro; Severo, Alice Antonella; Aragona, Pasquale (Frontiers in Pharmacology, 2021)
Aim of this retrospective study was to estimate the effect of oral supplementation with amino acids (AA) on corneal nerves regrowth after excimer laser refractive surgery with photorefractive keratectomy (PRK). Based on the pre and post-surgical treatment received, 40 patients with 12 months of follow-up were distributed in two groups: 20 patients had received oral AA supplementation 7 days before and 30 days after PRK, and 20 patients without AA supplementation, as untreated reference control. All patients followed the same standard post-operative topical therapy consisting of an association of antibiotic and steroid plus sodium hyaluronate during the first week, then steroid alone progressively decreasing during 30 days and sodium hyaluronate for the following 3 months. In vivo corneal confocal microscopy was used to evaluate the presence of sub-basal corneal nerve fibers during 12 months after PRK. Results have shown that sub-basal nerves regenerated significantly faster (p <0.05), and nerve fibers density was significantly higher (p <0.05) with a more regular pattern in the eyes of AA treated patients with respect to the untreated control group. Therefore, our data indicate that oral supplementation with AA improved significantly corneal nerve restoration after PRK and could thus be considered as an additional treatment during corneal surgical procedures.